Abrasion resistance of copper slag aggregate concrete designed by Taguchi method. (2022) - Panda, Swetapadma; Sarkar, Pradip
Abstract: The use of copper slag as fine aggregate in concrete construction will bring sustainability through the recycling of waste and conservation of natural resources. Nonetheless to improve the practical usage of copper slag as fine aggregate in concrete structures, it is necessary to have confirmation regarding the performance against abrasion failure of copper slag aggregate concrete with proper mix design. This study aims at evaluating, abrasion (wear) resistance of Copper Slag Aggregate concrete (CSA) which plays an important role as a concrete durability parameter, was investigated according to IS 1237. Four factors that mainly affect i.e. water-to-cement ratio, copper slag replacement percentage, quantity of natural sand and curing age were believed to achieve maximum resistance to compression and wear of CSA concrete using the Taguchi design experimental methodology including both statistical analysis of signal to noise ratio (SNR) and analysis of variance (ANOVA) technique. Based on the test results, CSA mixture with water-to-cement ratio of 0.38, copper slag percentage replacement of 80%, natural sand quantity of 365 kg/m 3 that had been cured for 91 days was optimally obtained mixture for maximum compressive strength and wear resistance. The results also showed that the wear depth of CSA concrete increased significantly as the amount of copper slag replacement and the cure period increased.